Advantages of the connective strategic narrative during the Russian–Ukrainian war - Zakharchenko, Artem (Frontiers in Political Science, 2025)
In this article, we expand the methodological approach to strategic narrative analysis based on the case of the contemporary Russian–Ukrainian war. Namely, we introduce the concept of a “connective strategic narrative.” Such a narrative is not intentionally constructed by elites but created by the “affective public” on social media—emotionally tied social media users, according to Papacharissi’s definition. We argue that the patriotic Ukrainian narrative about the war evolved in social media can be considered a connective strategic narrative that is more comprehensive than the “normal” strategic narrative shaped by authorities, while the pro-Russian social media war narrative is merely a reflection of the official strategic narrative. Based on social media data, we conducted a structural narrative analysis of both strategic narratives used in the ongoing war in Ukraine and deployed in the Ukrainian information space: the offensive pro-Russian narrative and the defensive Ukrainian narrative. The pattern for such analysis is based on Korostelina’s framework for national narrative analysis. Our analysis emphasizes the key differences between these narratives and shows that the Russian one has crucial disadvantages that prevent it from successfully engaging the Ukrainian people. Instead, as it was developed with the significant participation of ordinary citizens, the Ukrainian strategic narrative had the total advantage in the struggle for the attention of Ukrainians at the beginning of the full-scale invasion.